1999
DOI: 10.1007/s002619900483
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gastric polyps in familial amyloid polyneuropathy

Abstract: Amyloid masses of the gastrointestinal tract are very rare. A previously undescribed finding of multiple gastric polyps due to systemic amyloidosis is outlined in a patient with familial amyloid polyneuropathy. The relevant literature pertaining to gastric amyloidosis and mucosal masses is reviewed. Amyloidosis should be included in the differential diagnosis of target lesions in the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…There were no features of other cause for these polypoid lesions such as hamartoma, hyperplasia, or neoplasia; in fact, no mucosal or submucosal abnormality other than amyloid deposition was identified. Therefore, we concurred with Tada et al [5] and with Greaney et al [2], and propose that these polyps are caused by submucosal amyloid deposition. The present series as well as a review of the literature demonstrated that many neoplastic disease could be complicated by secondary amyloidosis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…There were no features of other cause for these polypoid lesions such as hamartoma, hyperplasia, or neoplasia; in fact, no mucosal or submucosal abnormality other than amyloid deposition was identified. Therefore, we concurred with Tada et al [5] and with Greaney et al [2], and propose that these polyps are caused by submucosal amyloid deposition. The present series as well as a review of the literature demonstrated that many neoplastic disease could be complicated by secondary amyloidosis.…”
Section: Discussionsupporting
confidence: 69%
“…But a case of the stomach amyloidosis, apparently confined to the stomach, is very rare. Greaney et al [2] reported the first case of multiple gastric polyps caused by submucosal amyloid deposition due to systemic amyloidosis. But in our case, the patient had no evidence of systemic amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Greaney et al reported multiple gastric polyps in a patient with familial amyloid polyneuropathy who presented with protracted nausea and vomiting. 6 Von Rosenvinge et al reported submucosal nodules and mucosal polyps in small intestine from duodenum to jejunum in patient with localized GI amyloidosis presenting with upper GI bleeding. 7 A similar case with localized GI amyloid polyps in the small intestine of a patient with primary amyloidosis was reported by Shimizu et al 8 A retrospective study by Menke et al in 769 patients with primary systemic amyloidosis found only 1 case with a gastric amyloid tumor.…”
Section: Discussionmentioning
confidence: 99%